Al-Muqniʿ fi ʼl-ḥisāb al-Hindī - Nasawī, Abu ʼl-Ḥasan (Miras Maktoob, ISBN: 9789004365452., 2019)
Abu ʼl-Ḥasan Nasawī was a mathematician and geometer of the 5th/11th century. He was a contemporary of Bīrūnī (d. 440/1048) and a student of Avicenna (d. 428/1037). Naṣīr al-Dīn Ṭūsī (d. 672/1274) mentions him in his works and so do others. Nasawī became known in the west through the publications of Franz Woepcke in the nineteenth century. Born in Rayy, Nasawī worked for the Buyid ruler Majd al-Dawla (d. 420/1029) and later for Sharaf al-Dawla, vizier to the Buyid ruler of Baghdad, Jalāl al-Dawla (d. 435/1044). In Nasawī's time, there were three types of arithmetic: finger-counting as used in business, a sexagesimal sytem with numbers denoted by letters of the Arabic alphabet, and an Indian system of numerals and fractions with decimal notation. The present work is about the Indian system and treats of four classes of numbers in four separate sections. This is Nasawī's own Arabic reworking of the Persian original, now lost.